Plasma metabolomics study of the hepatoprotective effect of glycyrrhetinic acid on realgar-induced sub-chronic hepatotoxicity in mice via 1H NMR analysis. (17th August 2017) - Huo, Taoguang; Fang, Ying; Zhang, Yinghua; Wang, Yanlei; Feng, Cong; Yuan, Mingmei; Wang, Shouyun; Chen, Mo; Jiang, Hong
Abstract: Ethnopharmacological relevance: Realgar, a type of mineral drug that contains arsenic, is concurrently used with Glycyrrhizae Radx et Rhizoma to reduce its toxicity in many Chinese herbal formulations. Glycyrrhetinic acid (GA) is the bioactive ingredient in Glycyrrhizae Radx et Rhizoma . In this study, the protective effects of GA on realgar -induced hepatotoxicity was investigated using 1 H nuclear magnetic resonance ( 1 H NMR)-based metabolomic approaches. Materials and methods: Mice were divided into control, GA, realgar, and GA and realgar co-administration groups. Their plasma samples were used for a metabolomics study. Results: GA can protect the mice against realgar -induced hepatotoxicity to some extent by relieving alterations in the clinical biochemical parameters and the damage to hepatocytes. Metabolic profiling via principal components analysis (PCA) and partial least squares-discriminant analysis (PLS-DA) indicated that the metabolic perturbation caused by realgar was reduced by GA. Six metabolites, including 3-hydroxybutyrate (3-HB), very low density/low density lipoprotein (VLDL/LDL), N -acetylglycoprotein (NAc), lactate, choline andD -glucose, were considered as potential biomarkers that are involved in the toxicity reduction effect of GA on realgar -induced hepatotoxicity. The correlation analysis showed that these potential biomarkers were all positively correlated with ALT and AST activities (correlation coefficient > 0.5). Lipid and energy metabolism pathways were found to be primarily associated with the hepatoprotective effect of GA. Conclusions: GA has an effective protection function by regulating the lipid and energy metabolism to liver injuries that are induced by realgar . Graphical abstract: